External and internal bone micro‐architecture in normal and Kienböck's lunates: A whole‐bone micro‐computed tomography study. Issue 6 (10th March 2014) - Low, Stephanie C.; Bain, Gregory I.; Findlay, David M.; Eng, Kevin; Perilli, Egon
ABSTRACT Kienböck's disease is idiopathic osteonecrosis of the lunate, leading to its fracture and collapse. This study compares internal and external bone micro‐architecture of normal and fractured lunates (Kienböck's), by using high‐resolution three‐dimensional (3D) micro‐computed tomography (micro‐CT) on the whole bone of the two lunate types, and histology. Fractured Kienböck‐diseased lunates were obtained from patients undergoing proximal‐row‐carpectomy, while normal cadaveric lunates served as controls. 3D‐micro‐CT‐imaging of control lunates revealed an encircling cortex surrounding trabecular bone. Trabeculae were arranged in a radial pattern, spanning from the distal to the proximal subchondral plate. Kienböck's lunates exhibited clear fracture lines, with fragmented bone, both proximally and distally, in areas the radially‐patterned trabeculae and enveloping cortex were absent, producing height loss. In trabecular bone, Kienböck's lunates revealed increased bone volume fraction, trabecular thickness and number, and decreased trabecular separation and structure model index. Histologically, Kienböck's lunates revealed osteonecrosis, as well as remodeling fronts with osteoblasts and osteoid surrounding bone marrow. Whole‐bone high‐resolution 3D examination of normal and Kienböck's diseased lunates contributes to a better understanding of micro‐architectural changes occurring in the pathology. © 2014 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:826–833, 2014.